2018
DOI: 10.1016/j.jmii.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of rectal carriage of Klebsiella pneumoniae amongst diabetic patients and their clinical relevance in Taiwan: A five-year prospective study

Abstract: Although nearly half of asymptomatic DM patients had rectal carriage of K. pneumoniae and one-third of them colonized by isolates belonging to the seven serotypes related to PLA, none of them subsequently developed PLA and colonized patients did not have higher risk of microbiologically confirmed bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The exact reason for this difference remains unknown. Intestinal carriage of virulent serotypes has been reported in Taiwan, Hong Kong, Singapore, and Korea (Siu et al, 2011;Chung et al, 2013;Huang et al, 2018). A recent study of samples from Madagascar, Cambodia, and Senegal showed a very different pattern of KP carriage (Huynh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The exact reason for this difference remains unknown. Intestinal carriage of virulent serotypes has been reported in Taiwan, Hong Kong, Singapore, and Korea (Siu et al, 2011;Chung et al, 2013;Huang et al, 2018). A recent study of samples from Madagascar, Cambodia, and Senegal showed a very different pattern of KP carriage (Huynh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[9] In addition, the majority of diabetic patients exhibit speci c vascular lesions, resulting in reduced blood ow velocity and impeding the mobilization and movement of white blood cells, consequently rendering diabetic patients at high risk for BLA. [10] The average size of the PLA was 40.82 cm²±34.93 cm². The maximum diameter of the PLA at admission indicates a long hospital stay and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous European studies have shown that Klebsiella pneumoniae and E. coli were the species most frequently responsible for ESBL secretion [3], especially K. pneumoniae, part of the natural intestinal microflora, but regarded as an opportunistic pathogen [4,5]. The colonization of biological tissues by K. pneumoniae frequently causes a large variety of diseases [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%